Helical Phase Inflation and Monodromy in Supergravity Theory - Tianjun Li; Zhijin Li; Dimitri V. Nanopoulos (Advances in High Energy Physics)
We study helical phase inflation which realizes “monodromy inflation” in supergravity theory. In the model, inflation is driven by the phase component of a complex field whose potential possesses helicoid structure. We construct phase monodromy based on explicitly breaking global U(1) symmetry in the superpotential. By integrating out heavy fields, the phase monodromy from single complex scalar field is realized and the model fulfills natural inflation. The phase-axion alignment is achieved from explicitly symmetry breaking and gives super-Planckian phase decay constant. The F-term scalar potential provides strong field stabilization for all the scalars except inflaton, which is protected by the approximate global U(1) symmetry. Besides, we show that helical phase inflation can be naturally realized in no-scale supergravity with SU(2,1)/SU(2)×U(1) symmetry since the supergravity setup needed for phase monodromy is automatically provided in the no-scale Kähler potential. We also demonstrate that helical phase inflation can be reduced to another well-known supergravity inflation model with shift symmetry. Helical phase inflation is free from the UV-sensitivity problem although there is super-Planckian field excursion, and it suggests that inflation can be effectively studied based on supersymmetric field theory while a UV-completed framework is not prerequisite.